The Donut : A Canadian History - Penfold, Steven, 1966- (Book collections on Project MUSE., 2008)
In Canada, the donut is often thought of as the unofficial national food. Donuts are sold at every intersection and rest stop, celebrated in song and story as symbols of Canadian identity, and one chain in particular, Tim Horton's, has become a veritable icon with over 2500 shops across the country. But there is more to the donut than these and other expressions of 'snackfood patriotism' would suggest. In this study, Steve Penfold puts the humble donut in its historical context, examining how one deep-fried confectionary became, not only a mass commodity, but an edible symbol of Canadianness. Penfold examines the history of the donut in light of broader social, economic, and cultural issues, and uses the donut as a window onto key developments in twentieth-century Canada such as the growth of a 'consumer society, ' the relationship between big business and community, and the ironic qualities of Canadian national identity. He goes on to explore the social and political conditions that facilitated the rapid rise and steady growth of donut shops across the country. Based on a wide range of sources, from commercial and government reports to personal interviews, The Donut is a comprehensive and fascinating look at one of Canada's most popular products. It offers original insights on consumer culture, mass consumption, and the dynamics of Canadian history.